2021
DOI: 10.1007/s00415-021-10752-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of CNS demyelination and COVID-19 infection: an updated systematic review

Abstract: Background Since the declaration of COVID-19 pandemic, several case reports of demyelination of both peripheral and central nervous systems have been published. The association between CNS demyelination and viral infection has long been documented, and this link was recently reported following SARS-CoV-2 infection as well. Objectives In this systematic review, we aim to investigate the existing literature on CNS demyelination associated with SARS-CoV-2, and the proposed pathophysiological mechanisms. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 83 publications
2
81
0
1
Order By: Relevance
“…Finally, in a recent review ( Ismail and Salama, 2021 ), 102 cases of CNS demyelination were reported in association with COVID-19 infection, from January 1, 2020, until June 15, 2021, while only 32 cases in association with COVID-19 vaccine were reported in a 10-month period. This is in line with robust evidence in literature, which documents a substantially higher risk of demyelination following infections, compared to the different types of vaccines ( García-Grimshaw et al, 2021 ; De Martino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent review ( Ismail and Salama, 2021 ), 102 cases of CNS demyelination were reported in association with COVID-19 infection, from January 1, 2020, until June 15, 2021, while only 32 cases in association with COVID-19 vaccine were reported in a 10-month period. This is in line with robust evidence in literature, which documents a substantially higher risk of demyelination following infections, compared to the different types of vaccines ( García-Grimshaw et al, 2021 ; De Martino et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiological mechanism remains unknown, but a para-infectious or post-infectious immune-mediated aetiology seems possible [ 78 ].…”
Section: Recommended Mri Protocol In Order To Investigate Patients With Covid-19 and Neurological Manifestationsmentioning
confidence: 99%
“…In a recent systematic review, patients with COVID-19 were found to have various patterns of brain and spinal cord demyelination resembling autoimmune neurologic disorders. ( Ismail and Salama, 2021 Aug 12 )…”
Section: Introductionmentioning
confidence: 99%
“…( Baig, 2020 Oct 21 , Butowt et al, 2021 ) Substantial evidence suggests COVID-19 causes a “cytokine storm” with proinflammatory cytokines, including IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, and IFN-γ that may cross the blood-brain barrier. ( Ismail and Salama, 2021 Aug 12 ) In this manner, the innate immunity mediators of the CNS such as macrophages, microglia, and astrocytes can be affected. Outside the CNS, hyperactivation of proinflammatory T cells, lymphopenia, decreased activity of regulatory T cells may also lead to antibody-mediated damage to the CNS and PNS.…”
Section: Introductionmentioning
confidence: 99%